Advances in human factors, business management and leadership : proceedings of the AHFE 2019 International Conference on Human Factors, Business Management and Society, and the AHFE International Conference on Human Factors in Management and Leadership, July 24-28, 2019, Washington DC., USA /: proceedings of the AHFE 2019 International Conference on Human Factors, Business Management and Society, and the AHFE International Conference on Human Factors in Management and Leadership, July 24-28, 2019, Washington DC., USA. ([2020]) - Unknown
No abstract available